2019
DOI: 10.1016/j.molcel.2019.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase 2 Recruits Replication Protein A to Sites of LINE-1 Integration to Facilitate Retrotransposition

Abstract: Long interspersed element-1 (LINE-1 or L1) retrotransposition poses a threat to genome integrity, and cells have evolved mechanisms to restrict retrotransposition. However, how cellular proteins facilitate L1 retrotransposition requires elucidation. Here, we demonstrate that single-strand DNA breaks induced by the L1 endonuclease trigger the recruitment of poly(ADP-ribose) polymerase 2 (PARP2) to L1 integration sites and that PARP2 activation leads to the subsequent recruitment of the replication protein A (RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 81 publications
(134 reference statements)
2
60
0
Order By: Relevance
“…This triggers the recruitment of RPA at L1 integration sites to facilitate retrotransposition. Interestingly, RPA can also guide the cytidine deaminase APOBEC3A to sites of L1 integration ( 254 ) that can generate a cytosine to thymine mutation. This is reminiscent of previous studies, which reported that RPA can interact with the AID to mediate somatic hypermutation and class switch recombination of immunoglobulin genes ( 46 , 255 ).…”
Section: Rpa In Other Aspects Of Dna Metabolismmentioning
confidence: 99%
“…This triggers the recruitment of RPA at L1 integration sites to facilitate retrotransposition. Interestingly, RPA can also guide the cytidine deaminase APOBEC3A to sites of L1 integration ( 254 ) that can generate a cytosine to thymine mutation. This is reminiscent of previous studies, which reported that RPA can interact with the AID to mediate somatic hypermutation and class switch recombination of immunoglobulin genes ( 46 , 255 ).…”
Section: Rpa In Other Aspects Of Dna Metabolismmentioning
confidence: 99%
“…In the nucleus, the main enzymes carrying out poly-ADP-ribosylation are poly(ADP-ribose) polymerase 1 (PARP1) and PARP2. These enzymes bind to the damaged DNA and subsequently generate poly-ADP-ribose (PAR) chains that act as recruitment signals for a range of DNA repair factors 4 6 . The role of poly-ADP-ribosylation is established in single-strand break repair (SSBR) and in alternative non-homologous end joining (aNHEJ) mechanisms, where the key proteins involved in the repair pathways are known to be recruited to the site of DNA damage in a PAR-dependent manner 7 12 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the interactions of PARP2 with the BER proteins have not been estimated quantitatively. Furthermore, the data on the affinity and activation of PARP1 and PARP2 towards damaged DNA indicate that PARP1 prefers earlier BER-intermediates, whereas PARP2 mostly acts on later ones (30, 31, 87). In addition, this study as well as literature data indicate functional dependence of various repair enzymes’ activities on PARylation and PAR synthesis (reviewed in 26).…”
Section: Discussionmentioning
confidence: 99%